Regression analysis on the chemical descriptors of a selected class of DPP4 inhibitors - Janairo, Jose Isagani B. (Animo Repository, 2010)
The activity of a selected class of DPP4 inhibitors was assessed using quantum-chemical and physical descriptors. Using multiple linear regression model, it was found that ΔE, LUMO energy, dipole, area, volume, molecular weight and ΔH are the significant descriptors that can adequately assess the activity of the compounds. The model suggests that bulky and electrophilic are desired. Furthermore a pair interaction between ΔE and dipole as well as for LUMO energy and dipole were determined. It is expected that the information derived herein will be beneficial for future design and development of DPP4 inhibitors.